Peranan Bisnis Makanan Dan Minuman Berbasis Home Industry Dalam Meningkatkan Kesejahteraan Keluarga Pelaku UMKM Di Kawasan Kuliner Monumen Ganggawa Kabupaten Sidenreng Rappang - Sumartan Sumartan; Nur Rahmah Wahyuddin (Universitas 45 Surabaya, 2023)
This study aims to describe the role of the home industry-based food and beverage business with raw materials and local products in improving the family economy and improving the standard of living for MSME actors in the Ganggawa Monument Court, Lakessi Village, Maritengngae District, Sidenreng Rappang Regency. This research is a field research using the survey method, namely the data collection method which was carried out by interview techniques and direct observation in the field with a total of 22 informants from home-scale culinary entrepreneurs (home industry). The data obtained and then analyzed with a qualitative descriptive approach. The data analysis technique uses welfare indicators according to the Central Bureau of Statistics for 2022. The results show that the home industry-based food and beverage culinary business plays a positive role in improving the welfare of the local community. Aside from being a source of income, the home industry is also able to absorb existing resources, namely being able to absorb local labor and resources, and being able to increase human resources through home industry production activities.